Solving Basic Problems Involving Brackets

Algebra: Solve for x Help

Home | Solve for x menu | Algebra menu

The easiest way to show you how to tackle these type of problems is by working out an example. The basic idea is to get the x-terms on one side of the equation and the constants on the other.

Example: Solve:

-8(6x + 5) = 3(8x + 1) + 173

Step 1: Get rid of the brackets using the distributive law. We get:

-8(6x + 5) = 3(8x + 1) + 173

-48x - 40 = 24x + 3 + 173

-48x - 40 = 24x + 176

Step 2: Get the x-terms on one side of the equation and the constants on the other side. First we subtract 24x from both sides:

-48x - 40 = 24x + 176

-48x - 40 - 24x = 24x + 176 - 24x

-72x - 40 = 176

Then add 40 to both sides:

-72x - 40 = 176

-72x - 40 + 40 = 176 + 40

-72x = 216

Step 4: Divide both sides by -72.

-72x = 216

-72x/-72 = 216/-72

x = -3

Our answer is -3.

DON'T FORGET! If you have something like 2x + 3 -(x + 5), this means the same thing as 2x + 3 -1(x + 5). So, when you expand this expression, you get 2x + 3 - 1x - 5 = 1x - 2 = x - 2